2022
DOI: 10.3389/fenrg.2021.812467
|View full text |Cite
|
Sign up to set email alerts
|

Optimal PID Tuning of PLL for PV Inverter Based on Aquila Optimizer

Abstract: Phase-locked loop (PLL) is a fundamental and crucial component of a photovoltaic (PV) connected inverter, which plays a significant role in high-quality grid connection by fast and precise phase detection and lock. Several novel critical structure improvements and proportional-integral (PI) parameter optimization techniques of PLL were proposed to reduce shock current and promote the quality of grid connection at present. However, the present techniques ignored the differential element of PLL and did not acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
(27 reference statements)
0
1
0
1
Order By: Relevance
“…To significantly guarantee a high-quality connection grid of a PV system, Guo et al [ 38 ] suggested a unique PID parameter tuning technique of PLL with AO. The AO was utilized to decrease power fluctuations and enhance grid connection quality.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%
“…To significantly guarantee a high-quality connection grid of a PV system, Guo et al [ 38 ] suggested a unique PID parameter tuning technique of PLL with AO. The AO was utilized to decrease power fluctuations and enhance grid connection quality.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%
“…By observing and imitating the predation process of the aquila, Abualigah et al [29] proposed the AO algorithm in 2021. Compared with other meta-heuristic algorithms, the AO exhibits considerable superiority in practical engineering problems [29][30][31][32]. The modeling process for the parameter optimization of MPKELM using the AO algorithm is as follows.…”
Section: Parameter Optimization Using Aquila Optimizermentioning
confidence: 99%
“…Extensive investigations have been carried out in the realm of power electronics and power conversion systems to optimize controller parameters. Diverse metaheuristic algorithms, such as atom search optimization (ASO) [ 36 ], weIghted meaN oF vectOrs optimizer (INFO) [ 37 ], hunger games search (HGS) optimizer [ 38 ], Aquila optimizer (AO) [ 39 ], particle swarm optimization [ 40 ], manta-ray foraging optimizer (MRFO) [ 41 ], chimp optimization algorithm (ChOA) [ [42] , [43] , [44] ], marine predators algorithm (MPA) [ 45 ], fuzzy whale optimization algorithm (FWOA) [ 46 ], grey wolf optimizer (GWO) [ 47 ], snow ablation optimizer (SAO) [ 48 ], and gorilla troops optimizer (GTO) [ 49 ] have been employed for this purpose. Snake optimizer (SO) [ 50 ] is a relatively new algorithm with limited utilization in power electronic converters and control in the literature at the time of writing this article.…”
Section: Introductionmentioning
confidence: 99%